Mecanismos intuitivo e racional e vieses comportamentais: evidências para o Brasil - Gomes, Anna Cecilia Chaves (2017)
The proposition that a processing composed of two systems - Intuitive and Rational - is responsible for the cognitive processes finds numerous references in the literature. Recent reviews suggest that the Intuitive System could be composed of a Set of Autonomous Systems (TASS) and the Rational by two levels of control: algorithmic and reflexive mentality. Although there is significant acceptance of the triple structure by artificial intelligence studies, current literature converges to dual processing, so there are still discussions about the components of the mind. Given that the systems would be responsible for promoting systematic deviations of normative reasoning (biases) and evaluation of heuristic attributes (heuristics), it has to be that the studies in the area can help in the understanding of the heuristic decision, therefore, more studies are needed, especially empirical ones, referring to the subject. Given the above, the present study treat to evaluate the multivariate architecture of the dominance of cognitive systems in the generation of behavioral biases. For this, a questionnaire was done with 2,958 participants from 21 public universities that measured the Representativity Heuristic, Anchoring, Availability Heuristic, Illusion of Control, Loss Aversion, Overconfidence, Optimism, Endowment Effect, Affect Heuristic, Conjunction Fallacy, Framing Effect, Mental Accounting, Disposition Effect, Intuitive System, and the Rational System. The scales were validated and analyzed by a Confirmatory Factor Analysis and then applied to the Structural Equation Model (SEM) and the invariance tests for sub-samples of the different genres, regions and professional qualification areas. Among the scales used, only Loss Aversion was not validated, probably because it was considered a clipping of the original (too large to be included). The Rational System was subdivided into 2 factors called Algorithmic and Reflexive, corroborating with studies about a tripartite structure. Two-dimensional structures were observed in the Optimism and Disposition Effect, according to what was observed in Bandeira et al. (2002) and Melo (2014), respectively. Concerning the specification of the structural model, it was noted that the Overconfidence, Optimism and Pessimism result from the same combination of systems, presenting indications that these could indeed appear together when analyzed empirically, as stated by Taylor and Brown (1988) and Barros and Silveira (2008). Anchoring would be occurring in what would appear to be a primming effect and the Mental Accounting showing to be partially responsible for causing the Disposition Effect, both observations according to the literature of the area. On the other hand, the Fallacy of the Conjunction, contrary to what was expected, did not demonstrate a significant relationship with the Heuristic of Representation, and this result may be due to the instrument, that measured the fallacy, be composed of issues that are heavily treated in the present day, thus allowing Availability to predominantly govern the bias. The SEM proved the influence of rational systems on the Affect Heuristic and Endowment Effect, in consonance with Kahneman (2012). Finally, when testing the invariance, it has been that, in all cases the rejection of the invariance hypothesis, proving that the cognitive aspects present a strong individual subjectivity and emphasize the importance of the profile for the understanding of the dominance of the systems.